PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING BERBANTUAN E- CROSSWORD PUZZLE TERHADAP HASIL BELAJAR SISWA PADA MATERI PANCASILA SISWA KELAS V LAB SCHOOL SD UNISMUH MAKASSAR - Ria Amelia Hasbullah; Jumiati Nur; Try Gustaf Said (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by problems found in the field, namely the low learning outcomes of students, particularly in the Pancasila material, where many students still do not know the symbols of Pancasila, the meaning of Pancasila, and how to apply its values in daily life. These problems were identified from the results of initial observations conducted prior to the research.This research employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The population of this study consisted of all students at Lab School SD Unismuh Makassar, while the sample included 19 fifth-grade students, comprising 13 males and 6 females. The instruments used in this study were an observation sheet and test items. The data analysis techniques applied were descriptive data analysis and inferential data analysis.The results of the study showed that the average pretest score was 55, while the posttest score increased to 76.31. Based on the paired samples test for hypothesis testing, the results indicated a t-value of −6.577 and a significance value (Sig. 2-tailed) of 0.000, which is lower than the significance level of 0.05 (0.000 < 0.05). Therefore, the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted.Based on these findings, it can be concluded that the game-based learning model assisted by an e-crossword puzzle has a significant effect on students’ learning outcomes in the Pancasila material for fifth-grade students at Lab School SD Unismuh Makassar.